Muslim Minority and Religious Freedom in Rantepao City, North Toraja Regency - Yulita Somba; Abdul Rahman (PT. Gudang Pustaka Cendekia, 2026)
This anthropological study examines the experiences of the Muslim minority in Rantepao City, North Toraja Regency, focusing on religious freedom and interfaith dynamics. In a predominantly Christian region, the Muslim community navigates its religious identity within a deeply rooted Torajan cultural landscape. Through ethnographic methods, including participant observation and in-depth interviews, this research explores how minority Muslims practice their faith, access public space, and maintain communal harmony. The findings reveal that religious freedom in Rantepao is negotiated through a balance of cultural assimilation and religious preservation. While formal rights are generally respected, subtle social boundaries exist, particularly regarding religious expression and ritual intersections with traditional Torajan customs (Aluk To Dolo). This study highlights the resilience of the Muslim minority and demonstrates how local cultural mechanisms facilitate daily coexistence, offering crucial insights into religious tolerance and minority-majority relations in contemporary Indonesia.